2005
DOI: 10.1002/hlca.200490292
|View full text |Cite
|
Sign up to set email alerts
|

Rationale on the Abnormal Effect of Temperature on the Enantioselectivity in the Asymmetric Borane Reduction of Ketones Catalyzed by L‐Prolinol

Abstract: The effect of temperature on the enantioselectivity of the oxazaborolidine-catalyzed asymmetric borane reduction of ketones was investigated in the presence of (5S)-3-oxa-1-aza-2-borabicyclo[3.3.0]octane ( (3aS)-tetrahydro-1H,3H-pyrolo[1,2-c][1,3,2]oxazaborole; 1a) and its 2-methoxy derivative (1b) as catalysts, which were synthesized from l-prolinol with borane and trimethyl borate, respectively. The results indicate that the two catalysts induce a different temperature-dependent enantioselectivity. The enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
6
0
4
Order By: Relevance
“…[12] l-Prolinol-derived 1,3,2-oxazaborolidine catalysts prepared from l-proline and giving the reduction product with moderate enantiomeric excess (ee) values were also studied. [13] Taking note of these reports we selected amino acids l-Leu (4 a), l-Phe (4 b), and l-Val (4 c) with a primary amino functionality as starting compounds for realization of the proposed one-pot reaction sequence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] l-Prolinol-derived 1,3,2-oxazaborolidine catalysts prepared from l-proline and giving the reduction product with moderate enantiomeric excess (ee) values were also studied. [13] Taking note of these reports we selected amino acids l-Leu (4 a), l-Phe (4 b), and l-Val (4 c) with a primary amino functionality as starting compounds for realization of the proposed one-pot reaction sequence.…”
mentioning
confidence: 99%
“…It was expected that B À OMe derivatives might perform better than the B-unsubstituted oxazaborolidines. [13,15] Notably, preliminary studies (see Table S3 in the Supporting Information) demonstrated that the use of 0.6 equiv of B-A C H T U N G T R E N N U N G (OMe) 3 (relative to the in situ generated amino alcohols 5 a-c, taking into consideration their theoretically possible yield from Table 1) was crucial to obtain good yield and enantioselectivity in the reduction of acetophenone. Therefore, B À OMe-derived oxazaborolidines 6 a-c were prepared in situ by addition of BA C H T U N G T R E N N U N G (OMe) 3 (0.6 equiv) to 5 a-c and stirring for 1 h at the desired temperature (RT or 60 8C).…”
mentioning
confidence: 99%
“…1) die meisten Veränderungen der geminalen Substituenten einen ungünstigen Einfluss auf die Enantioselektivität nehmen. 13 und 14) [31] nicht bestätigt werden. 2), aber auch für ortho-substituierte Aryl-(Nr.…”
Section: Nrunclassified
“…Dies gilt für den a-Naphthylrest (Nr. [31] Jedenfalls sind die von Prolinol abgeleiteten Oxazaborolidine, die Phenylethanol mit 20-60 % ee liefern, den Oxazaborolidinen auf der Basis von Diphenylprolinol bezüglich der Enantioselektivität definitiv unterlegen und weniger effizient als diese. 3 und 4) und 2-Thienylgruppen (Nr.…”
Section: Nrunclassified
See 1 more Smart Citation